Harrison's manual of medicine for PDA - Eugene, Braunwald (New York : Mc Graw-Hill, 2003)
The Harrison's manual of medicine provides practitioners with the key elements needed to diagnose and treat the major diseases that are encountered in day-to-day medical practice
System requirements: PALM: Handheld Device: Palm OS 3.x or later 620K of available memory. Memory cards not supported Desktop Computer: Windows OS95, 98, ME, 2000, XP, or NT 4.0 Workstation (SP3). HotSync Manager (or equivalent), version 3.01 or later. Connection to the Internet POCKET PC: Handheld Device: Win CE 3.0 or above (e.g., Pocket PC 2000, Pocket PC 2002, or above. A StrongARM processor. 850K of available memory. Memory cards are supported Desktop Computer: Windows OS 95, 98, ME, 2000,XP, or NT 4.0 Workstation (SP3). ActiveSync 3.1 or later. Connection to the internet.
Keywords: Clinical Medicine -- handbooks; Internal Medicine -- Handbooks